2022
DOI: 10.4102/phcfm.v14i1.3746
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of resources available for postgraduate family medicine training at a South African university

Abstract: Background: Clinical training is one of the roles of family physicians (FPs) in decentralised postgraduate training. Effective training requires skilled trainers and sufficient resources. Little is known about the resources available for decentralised clinical training in district health systems in low- to middle-income countries, especially in sub-Saharan Africa.Aim: To explore FPs’ and registrars’ perceptions of the available resources in a decentralised postgraduate family medicine (FM) training programme.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Perceptions regarding availability of resources for training were similar to that in a recent study from South Africa in which family medicine registrars (residents) reported shortages of resources such as training tools (e.g. ECG), Internet availability, and training space [34]. In both studies, residents observed that essential equipment were unavailable and hindered their training because they perceived that they could not develop mastery of skills needed in working with the lacking equipment.…”
Section: Discussionsupporting
confidence: 65%
“…Perceptions regarding availability of resources for training were similar to that in a recent study from South Africa in which family medicine registrars (residents) reported shortages of resources such as training tools (e.g. ECG), Internet availability, and training space [34]. In both studies, residents observed that essential equipment were unavailable and hindered their training because they perceived that they could not develop mastery of skills needed in working with the lacking equipment.…”
Section: Discussionsupporting
confidence: 65%
“…WBA needs engaged stakeholders, and its implementation is deeply in uenced by the context in which it is practised, being grounded in the social realities of the workplace context (18,19). A core premise that informs this practice is the quality of the feedback provided by supervisors to registrars in the clinical spaces, which implicates the institutional culture and relationship between supervisors and registrars as key factors that in uence the assessment outcomes (20,21). Student engagement in the process of WBA is also integral to its success, and attention should be paid to the social nature of learning (22).…”
Section: Introductionmentioning
confidence: 99%